Transcriptional regulation of the human insulin gene is dependent on the homeodomain protein STF1/IPF1 acting through the CT boxes. - Petersen, H V (1994)
Insulin gene transcription is a unique feature of the pancreatic beta cells and is increased in response to glucose. The recent cloning of insulin promoter factor 1 (IPF1) and somatostatin transcription factor 1 (STF1) unexpectedly revealed that these are mouse and rat homologues of the same protein mediating transactivation through binding of CT box-like elements in rat insulin 1 and somatostatin promoter/enhancer regions, respectively. By using oligonucleotides representing each of the three CT boxes of the human insulin (HI) gene enhancer and nuclear extracts from the mouse islet tumor cell lines beta TC3 and alpha TC1, we have identified a beta-cell-specific binding activity as reported for IPF1, which has maximal affinity toward the CT2 box. However, in pluripotent, HI-transfected rat islet tumor cells, NHI-6F, this binding activity is present prior to induction of (human) insulin gene transcription. Its migration is identical to that of in vitro translated STF1 in electrophoretic mobility-shift assays; it is specifically recognized by anti-STF1 antibodies and has an apparent molecular mass of 46 kDa. Mutation of the CT2 box decreases transcriptional activity of a HI reporter plasmid by approximately 65% in beta TC3 cells and blocks the glucose response in isolated newborn rat islet cells. Furthermore, cotransfection with STF1 cDNA into the glucagon-producing alpha TC1 cells increases the activity of the HI enhancer 4- to 5-fold, suggesting that STF1/IPF1 can confer on alpha TC1 cells the ability to transcribe the HI gene. We conclude that STF1/IPF1 is a necessary but not sufficient key regulator of insulin gene activity, possibly also involved in glucose-regulated transcription.